Water quality study of melaka river using WQI, remote sensing and GIS / Rasyidah Abd Aziz - Abd Aziz, Rasyidah (2014)
Melaka River is a popular tourism attraction in Melaka and it is crucial to ensure it is clean and crystal clear. In Malaysia, water pollution is identified using Water Quality Index (WQI), by the Department of Environment (DOE), since 1986. The WQI parameters are Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), Ammoniacal Nitrogen (NH3-N), Suspended Solids (SS), and pH. Additional parameters of Temperature, Colour, Turbidity, Level (Depth) and Conductivity were used as support data. SPOT-5 Pansharp Supermode All Bands as near-real-time data provides an ideal 2.5m high resolution within appropriate availability time provided with the Digital Elevation Model (DEM). The Geographical Information System (GIS) used as a mapping tool to conclude and better gathered all information and current condition of the river water and the potential pollution sources can be monitored. The combination of on-site data, laboratory testing data and satellite imagery data could support each method limitations that produce GIS mapping and analysis for future water quality control and management. The correlation of all six parameters of pH, SS, BOD, COD, NH3-N and DO versus Band 1, Band 2, Band 3 and Band 4 show low values of regressions with the highest reading of 0.2970. All six parameters were being estimated using the SPOT 5 image. The regression values indicated that the best band to estimate the value of NH3-N is Band 3, pH, BOD, COD and DO are using Band 2 and SS using Band 1. All additional parameters of Level, Colour, Conductivity, Temperature and Turbidity versus Band 1, Band 2, Band 3 and Band 4 show even lower values of regressions 0.1957. All five additional parameters were also being estimated using the SPOT 5 image. The regression values above indicated the best band to estimate Level is Band 4, Colour is Band 3, Conductivity and Temperature is Band 2 and Turbidity is Band 1. Red Zone Mapping of Very Critical parameters of DO, BOD, COD, NH3-N, Temperature and Conductivity show that those parameters are the top priority to be monitored and managed.